Calibration of hydrophones using a frequency domain filter processing method: theory and experiment. (15th December 2020) - Chen, Yi; Yang, Liuqing; Zhou, Lisheng; Jin, Xiaofeng; Jia, Guanghui
Abstract: To eliminate the interferences coming from the boundaries of a water tank and extend its low frequency calibration limit, a frequency domain filter processing (FDFP) method is proposed for hydrophone calibration measurements. The frequency domain filter function is designed according to the a priori spatial position of projector and hydrophone pair in a water tank. A simultaneous comparison method is used for calibration, and a wideband pink noise pulse signal is transmitted. After application of the FDFP method, the transfer impedances of projector and hydrophone pairs in a quasi-free-field are obtained, and interferences reflected from the boundaries of the water tank are effectively eliminated. To verify the FDFP method, an experimental system is established for calibration of the free-field sensitivity of a TC 4033 hydrophone. For a non-anechoic water tank of 1.5 m × 0.88 m × 0.90 m, the lowest calibration frequency is extended from 20 kHz to 3.15 kHz, and the calibration result is consistent with the free-field reciprocity calibration result obtained in an anechoic water tank of 50 m × 15 m × 10 m in the frequency range 3.15 kHz to 31.5 kHz.